A Polar and Nucleotide-Dependent Mechanism of Action for RAD51 Paralogs in RAD51 Filament Remodeling - Taylor, Martin R G; Špírek, Mário; Jian Ma, Chu; Carzaniga, Raffaella; Takaki, Tohru; Collinson, Lucy M; Greene, Eric C; Krejci, Lumir; Boulton, Simon J (Molecular cell, 2016)
Central to homologous recombination in eukaryotes is the RAD51 recombinase, which forms helical nucleoprotein filaments on single-stranded DNA (ssDNA) and catalyzes strand invasion with homologous duplex DNA. Various regulatory proteins assist this reaction including the RAD51 paralogs. We recently discovered that a RAD51 paralog complex from C. elegans, RFS-1/RIP-1, functions predominantly downstream of filament assembly by binding and remodeling RAD-51-ssDNA filaments to a conformation more proficient for strand exchange. Here, we demonstrate that RFS-1/RIP-1 acts by shutting down RAD-51 dissociation from ssDNA. Using stopped-flow experiments, we show that RFS-1/RIP-1 confers this dramatic stabilization by capping the 5' end of RAD-51-ssDNA filaments. Filament end capping propagates a stabilizing effect with a 5'→3' polarity approximately 40 nucleotides along individual filaments. Finally, we discover that filament capping and stabilization are dependent on nucleotide binding, but not hydrolysis by RFS-1/RIP-1. These data define the mechanism of RAD51 filament remodeling by RAD51 paralogs.
Keywords: Protein Binding; multiproteinové komplexy; Intermediate Filaments; Rad51; jednovláknová DNA; homologous recombination; intermediární filamenta; DNA repair; Recombinational DNA Repair; DNA vazebné proteiny; genome stability; rekombinační oprava DNA; Rad51 Recombinase; rekombinasa Rad51; Carrier Proteins; vazba proteinů; Caenorhabditis elegans Proteins; proteiny Caenorhabditis elegans; DNA, Single-Stranded; filaments; DNA-Binding Proteins; Rad51 paralogs; transportní proteiny; Multiprotein Complexes